2010
DOI: 10.1111/j.1524-4725.2010.01719.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Striae Distensae Using an Ablative 10,600-nm Carbon Dioxide Fractional Laser

Abstract: Our observations demonstrated that the use of CO₂ FS can have a positive therapeutic effect on late-stage striae distensae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
2
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 31 publications
(59 reference statements)
8
76
2
7
Order By: Relevance
“…They found that the laser was effective in decreasing the size of the striae, a finding that we did not report. Lee et al [17] studied the effect of a fractional CO 2 laser on 27 female patients with skin type IV who had striae alba. They concluded that the laser had a positive therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the laser was effective in decreasing the size of the striae, a finding that we did not report. Lee et al [17] studied the effect of a fractional CO 2 laser on 27 female patients with skin type IV who had striae alba. They concluded that the laser had a positive therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the possible therapeutic and beneficial effects of different types of laser in the treatment of striae distensae [12,[15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…7 Since, as mentioned, stretch marks are thought to be dermal scars, CO 2 FL could theoretically be helpful. Lee et al 8 reported that of 27 patients treated with ablative CO 2 FL, 59% showed marked to near-total improvement. Shin et al 9 also reported that ablative CO 2 FL was effective.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed more side effects of treatment than the previous studies. Lee et al 8 state that only a few patients had mild post-therapy hyperpigmentation. However, in our study, 53.8% of patients had post-therapy hyperpigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Microdermabrasion can be a useful therapeutic option with a possible stimulatory effect on type I procollagen formation [8]. Several light and laser modalities such as intense pulsed light [9], pulsed dye laser [10], copper bromide laser [11], radiofrequency device [12], excimer laser [13], and fractional CO 2 laser [14] have been demonstrated to achieve some effect in treating striae distensae; however, postinflammatory hyperpigmentation is of major concern in darker skin types.…”
Section: Introductionmentioning
confidence: 99%